Clinical Intervention Increases Rational Use of Proton Pump Inhibitors in the General Surgery Department - Chen, Qiying; Wang, Qiaohong; Zhang, Yin (Frontiers in Pharmacology, 2022)
The research aims to study the role of the clinical pharmacist in the rational use of PPIs in the general surgery department. All patients were collected from the general surgery department of a tertiary hospital. A single-center prospective study was conducted to compare the differences of PPIs overall reasonable rate, the proportion of PPIs use without indication, utilization rate, average DDDs, drug cost, PPIs cost, cost-effectiveness analysis of clinical pharmacists' intervention between the intervention group (538 cases) and the control group (536 Cases). The intervention group used the Pareto Diagram + fishbone diagram analysis combined with the PDCA cycle. SPSS analyzed all cases. The overall rational rate of PPIs in the intervention group was significantly higher than that in the control group (P<0.01); the proportion of PPIs use without indication, the utilization rate, the average DDDs, drug cost, and PPIs cost in the intervention group were significantly lower than those in the control group (P<0.05). The result of cost-effectiveness analysis in improving the overall rational rate of PPIs in the intervention group was positive and economical. The intervention of clinical pharmacists on the rational use of PPIs in the general surgery department could significantly increase the overall rational rate of PPIs and reduce the proportion of PPIs use without indication, the utilization rate, the average DDDs, drug cost, and PPIs cost. The cost-effectiveness analysis suggests that pharmacists' intervention improved the PPI's overall rational rate.